A multi-method sensory approach to characterize pasteurized ready-to-eat sausages in the Indonesian market: From attribut escreening totemporal dynamics - Shaski Ghina Nurfauziyah; Dase Hunaefi; Faleh Setia Budi; Rifa Adawiyah Atmawanjaya; Dewi Sarastani; Andi Early Febrinda; Mrr. Lukie Trianawati; Rianti Dyah Hapsari; Philipp Lawrence Fuhrmann; Iryna Smetanska (jurnal1, 2026)
Ready-to-eat (RTE) sausages have become increasingly popular in the Indonesian market due to changing consumer preferences and growing demand for convenient, high-quality protein sources and innovative food products. However, comprehensive sensory studies evaluating these products in the local context remain limited. This study aimed to characterize the sensory attributes and temporal flavor dynamics of five commercial pasteurized RTE sausage brands using a multi-method sensory approach. A total of 144 untrained consumers participated in a Check-All-That-Apply (CATA) and 24 trained panelists conducted Temporal Dominance of Sensations (TDS) evaluations. CATA results revealed distinct sensory profiles among products, with Product 4 showing the strongest alignment with the ideal profile, and Product 2 receiving the highest overall liking score. TDS results further complemented these findings, where Product 2 showed a more prolonged and intense meaty flavor. Product 4 displayed more dynamic sensory transitions during mastication, whereas the lower-liked Product 5 exhibited less intense and less clearly defined dominance patterns. Penalty analysis identified fishy aroma, starchy flavor, and bitter aftertaste as key drivers of disliking. The integration of CATA and TDS sensory data highlights not only which attributes are important, but also how and when they are perceived. These findings may support future food product reformulation and sensory-driven innovation to improve consumer acceptance of innovative RTE protein products.